Circadian Variation in Frequency of Stroke in Bangladesh: a Hospital Based Cross Sectional Study - Hossain, Ahmed Manadir; Saha, Radheshyam; Tarafder, Binoy Krishna; Salam, Md Abdus; Islam, Md Rafiqul; Saleh, Mohammed Abayedeen; Rahman, Mahbubur (Faridpur Medical College Journal, 2015)
A hospital based cross sectional study was carried out to analyze diurnal variation of stroke and their association to sleep awake cycle. Four hundred and two patients of stroke admitted in different Medicine Units of Faridpur Medical College and Dhaka Medical College Hospitals from July 2012 to June 2013 were chosen using purposive sampling technique. Enrolled patients were with their first stroke, subsequently proved by CT scan of brain. The initial clinical diagnosis of stroke was made from history and examination obtained from the patient himself or from his/her attendant. The time of onset of stroke was recorded by attending doctor at the time of assessment and recorded on a fixed proforma. Patient who could not give history properly or had no responsible attendant and who had history of head injury, intracranial space occupying lesion or bleeding disorder were excluded from the study. Age ranged from 25 years to 98 years with mean age of 62.02 years (±SD 11.75 years). Out of 402 patients 59.7% suffered from ischemic stroke. Highest incidence of stroke (26.9%) occurred between 4:01am to 8:00 am and lowest (7.5%) between 8:01 pm to 12:00 am. Among the subtypes, ischaemic stroke has shown a single peak incidence at 4:01 to 8:00 am and lowest between 8:01 pm to 12:00 am. 50 % of ischaemic stroke cases developed between 0:01 am to 8:00 am. In this study, maximum number of patients developed hemorrhagic stroke between 4:01 am to 8:00 am (25.9%) and lowest number developed hemorrhagic stroke between 12:01 pm to 4:00 pm (9.3%). This study confirms the diurnal variation of both hemorrhagic and ischaemic stroke in Bangladesh and most of them occurs in early morning after wakening. Faridpur Med. Coll. J. 2014;9(2): 80-83